2017
DOI: 10.21512/bbr.v8i2.2090
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flight and the Economic Growth: Evidence from Nigeria

Abstract: This research examined the impact of capital flight and its determinants on the Nigerian economy using the Autoregressive Distributed Lag (ARDL) model to analyze data source from the period of 1981 to 2015. The variables included current account balance, capital flight, foreign direct investments, foreign reserve, inflation rate, external debt, and the real gross domestic product. It was to examine the existence of a long run relationship among the variables studied. The result indicates that capital flight ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Some even argue that capital flight has no significant effect on economic growth. The study by Lawal et al (2017) examined the impact of capital flight and its determinants on the Nigerian economy between 1981 and 2015, using the auto regressive distributed lag (ARDL) model. Findings revealed that there is existence of a long-run relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some even argue that capital flight has no significant effect on economic growth. The study by Lawal et al (2017) examined the impact of capital flight and its determinants on the Nigerian economy between 1981 and 2015, using the auto regressive distributed lag (ARDL) model. Findings revealed that there is existence of a long-run relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many empirical studies have examined the nexus between capital flight and economic growth across countries (Lawal et al, 2017;Akinwale and Obagunwa, 2017). Only few studies have examined the relationship between capital flight and economic development (Lan et al, 2010;Liew et al, 2016;Cheung and Qian, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the devaluation of currency on the economic behaviour of nations has remained a subject of hot debate that is inconclusive. Some scholars have documented the existence of positive impact of devaluation on economic growth (Tang & Zhang, 2012;Alston & Mueller, 2016;Doan & Gente, 2014;Lawal et al, 2017). Meanwhile, the others have noted the different result (Addison & Baliamoune-Lutz, 2017;Damania, Russ, Wheeler, & Bara, 2018;Lawal, Nwanji, Asaleye, & Ahmed, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It resulted in import intensity, distribution costs, the income level of destination countries, and foreign ownership playing significant roles. For more reference, see Berman, Martin, and Mayer (2012); Burstein and Gopinath (2014); Tang and Zhang (2012); Alston and Mueller (2016); Doan and Gente (2014); Bodart, Candelon, and Carpantier (2015); Bordo, Choudhri, Fazio, and MacDonald, (2017); Bouvet, Ma, and Van Assche (2017); Chen, Choi, and Devereux (2015); Chen, and Juveral, (2016); Dellas and Tavlas (2013); Katusiime, Shamsuddin, and Agbola (2015); Mueller and Mueller (2016), Lawal et al, (2017); Adedoyin, Babalolam, Otekunri, and Adeoti (2016).…”
Section: Introductionmentioning
confidence: 99%